2009
DOI: 10.1097/tp.0b013e31819c83b5
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Augmentation Improves Condition of Guinea Pig Hearts After 4 hr of Cold Ischemia

Abstract: Augmenting HTK with human albumin improves endothelial integrity and heart performance after 4 hr cold ischemia, because of a marked protection of the endothelial glycocalyx. For the prevention of acute and chronic graft failure, the glycocalyx might represent a new target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 41 publications
0
84
0
3
Order By: Relevance
“…It has been used as a nonmetabolisable impermeate added to perfusates during post-ischemic reperfusion to reduces cell edema (i.e., cell swelling) by retaining water outside myocytes (22). In our Langendorffperfused ventricle preparations, mannitol perfusion was associated with increased V IS (Fig.…”
Section: Perfusate Effects On Myocardiummentioning
confidence: 88%
See 1 more Smart Citation
“…It has been used as a nonmetabolisable impermeate added to perfusates during post-ischemic reperfusion to reduces cell edema (i.e., cell swelling) by retaining water outside myocytes (22). In our Langendorffperfused ventricle preparations, mannitol perfusion was associated with increased V IS (Fig.…”
Section: Perfusate Effects On Myocardiummentioning
confidence: 88%
“…In contrast, mannitol is a small molecule (molecular weight, 182.17) that raised perfusate osmolarity (see METHODS) and should extravasate freely (22). It has been used as a nonmetabolisable impermeate added to perfusates during post-ischemic reperfusion to reduces cell edema (i.e., cell swelling) by retaining water outside myocytes (22).…”
Section: Perfusate Effects On Myocardiummentioning
confidence: 99%
“…Albumin attenuated glycocalyx shedding during 4 h of cold ischaemia and reperfusion in guinea pig hearts, reducing interstitial oedema and intracoronary adhesion of leucocytes [40]. Albumin dilates coronary arteries compared with HES, possibly by enhancing NO production in response to shear stress: vasodilation by albumin was reduced when NO synthase was blocked and when the glycocalyx was damaged [18].…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 99%
“…95 Albumin can be used in severe sepsis and septic shock when patients require substantial amounts of crystalloids, 1 but it should not be used in patients with traumatic brain injury. 95,96 Moreover, instead of its theoretical benefits in septic patient, 97,98 the SAFE study showed no significant difference between saline and albumin in ICU patients. 96 Semisynthetic colloids as hydroxyethyl starch solutions should not be used because of the increased mortality and risk of renal replacement therapy.…”
Section: Septic Shock: Pathophysiology and Hemodynamic Resuscitationmentioning
confidence: 99%